Childhood Depression : a Place for Psychotherapy - Trowell, Judith; Miles, Gillian; Rustin, Michael (Tavistock Clinic series., 2011)
This title is based on the results of a project based at the Tavistock Clinic in London which set out to explore whether children and young people aged nine years to fifteen years suffering from depression could be helped using brief focused psychodynamic psychotherapy together with parent work and family therapy. There were also centres in Athens, Greece and Helsinki, Finland, and in this way the clinicians had sufficient subjects from which to compare the interventions and check for any possible cultural differences in the results. Most of the children and young people studied showed a notic.